Pengembangan Flipbook Bermuatan Literasi Numerasi untuk Meningkatkan Kemampuan Komunikasi Matematis - Devi Nurtria Sandy; Yus Mochamad Cholily; Zukhrufurrohmah Zukhrufurrohmah; Siti Khoiruli Ummah (Jurnal Tadris Matematika, 2022)
Based on the interview with the mathematics teacher in grade 9 of Junior High School in Malang, learning media used in school was limited, especially in material of transformation. This cause the students have difficulty communicating mathematical ideas when solving the problems. The purpose of this study is to develop an e-module learning media in the form of a flipbook to improve students’ mathematical communication skills. Research and development of the media was carried out using the ADDIE model. The results of the validation test that carried out by the lecturers and teachers obtained a very valid category value. The results of the effectiveness test using the N-Gain value is 0.66 included in the medium improvement category, it means that mathematical communication skills increase after being given flipbook learning media. The results of the practicality test received a positive response with an average of 79%. Based on the results of the validation, effectiveness, and practicality tests, it can be concluded that the development of flipbook learning media is valid, effective, and practical to use in teaching and learning activities to improve students’ mathematical communication skills.